1950
DOI: 10.1177/004051755002000502
|View full text |Cite
|
Sign up to set email alerts
|

Wax Content as Related to Surface Area of Cotton Fibers

Abstract: Among a group of 62 essentially unweathered fiber samples from American upland cotton plants of different inherent and environmental background, percent wax was found to be rather closely proportional to surface area per unit weight of fiber as determined by the air-flow method of Sullivan and Hertel [22]. The weight of wax per unit of fiber surface was thus a relatively constant quantity, although not an absolutely constant one, among these samples. Results of melting-point determinations did not suggest the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1952
1952
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Cotton fiber wax content varies significantly among different varieties. Various studies have reported a strong positive relationship between cotton fibers wax content and their surface area [73,74,[172][173][174]. El Mogahzy showed that the frictional properties of cotton fibers are influenced by their wax content [73].…”
Section: Nanofricitonal and Nanomechanical Properties Of Cotton Fibersmentioning
confidence: 99%
“…Cotton fiber wax content varies significantly among different varieties. Various studies have reported a strong positive relationship between cotton fibers wax content and their surface area [73,74,[172][173][174]. El Mogahzy showed that the frictional properties of cotton fibers are influenced by their wax content [73].…”
Section: Nanofricitonal and Nanomechanical Properties Of Cotton Fibersmentioning
confidence: 99%
“…[93][94][95][96] Only a limited amount of work in establishing the quantitative and qualitative differences in wax content among different cotton samples to the varietal and/or environmental background of the plant has been published. Most of these studies [97][98][99] found that the chemical components of wax from different varieties and species were very similar. However, in two circumstances Marsh et al 98 and Gordon et al 99 cottons with waxes that were significantly different in content were found.…”
Section: Wax Contentmentioning
confidence: 99%
“…Most of these studies [97][98][99] found that the chemical components of wax from different varieties and species were very similar. However, in two circumstances Marsh et al 98 and Gordon et al 99 cottons with waxes that were significantly different in content were found. Marsh et al 98 found wax from cotton exposed to weathering had a lower melting point, and higher wax content as measured by the Conrad method, whilst Gordon et al 99 found some low Micronaire cotton in the set examined had much higher concentrations of hydrocarbon or alkane waxes.…”
Section: Wax Contentmentioning
confidence: 99%
“…The results after chloroform extractions are shown in Table V. It is seen that all samples retained very good water-repellency through extraction. The finish produced was resistant to laundering, [11][12][13][14] launderings being required to remove the water-repellency (Figure 2). …”
Section: Stearamidomethylpyridinium Chloridementioning
confidence: 99%
“…Water-repellency has been observed by other workers with amounts of this mag- nitude. Marsh et al [13], for example, working with a number of varieties of cotton, found that raw cotton contains 0.5 % to 0.7% wax and is notably water-repellent until scoured or mechanically damaged. Walker [20] calculated that approximately 1% of water will completely cover the available surface of cotton fibers.…”
Section: Stearamidomethylpyridinium Chloridementioning
confidence: 99%